Experimental inconsistencies undermine accurate characterization of microplastics and identification of environmental drivers:a metadata analysis in Chinese aquatic environment - Qinwei Chen; Peng Wang; Ru Liu; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Minghua Nie (Ecological Indicators)
Microplastic pollution in surface waters is a global concern, but the driving factors remain unclear. The characteristics of microplastics were assessed at 2,430 sampling sites in Chinese aquatic environments using published data. Geographical detectors, correlation analysis, analysis of variance, correspondence analysis, and structural equation modeling were used to examine both the effects of human activities and natural processes on microplastic characteristics and the potential influence of experimental methods on these characteristics. The abundance of microplastics was found to be significantly influenced by both human activities and natural processes, including farmland areas, landscape connectivity and annual mean precipitation. Furthermore, significant variations in the characteristics of microplastics were observed between experimental treatments, with the sampling method identified as a key factor influencing their observed abundance. Microplastic abundance showed a significant negative correlation with sample size, but no clear linear relationship with sieve aperture. The influence of the experimental methods reduced the association between the characteristics of microplastics and both human activities and natural processes. In water, the experimental methods reduced the correlation between natural processes and microplastic characteristics by 70 %, and in sediment by 39.6 %. However, the impact of human activities proved to be more complex, with the correlation increasing in water but decreasing by 47.9% in sediment. These findings suggest that variations in experimental methods can distort the accurate depiction of microplastic characteristics, obscuring their true relationship with environmental factors. This experimental inconsistency creates confusion about how microplastics spread and behave in the environment. This highlights the necessity for the development of standardized experimental methods and protocols for microplastics.